Transformasi pembelajaran di madrasah: Integrasi blended learning dan hybrid learning - Mustofa, Labib; Rosyidah, Amiliya Nur; Susilawati, Samsul (Maliki Interdisciplinary Journal, 2025)
The integration of blended and hybrid learning models has gained significant importance in modern education, particularly in madrasah settings. Blended learning combines face-to-face and online instruction, offering flexibility and enhancing the learning experience by accommodating various student needs. Hybrid learning, on the other hand, merges classroom interaction with digital platforms, allowing for a more adaptive and personalized approach to learning. Both methods have been shown to improve student engagement, facilitate access to diverse learning resources, and enhance the mastery of both academic and religious subjects in madrasah. However, the implementation of these learning models faces several challenges, including limited technological infrastructure, disparities in digital literacy among teachers and students, and the need to align digital content with Islamic educational values. This study examines the impact of blended and hybrid learning on educational outcomes in madrasahs and explores strategies to optimize their application, supporting holistic learning experiences that encompass academic excellence and spiritual development.